1978
DOI: 10.1136/jcp.31.3.259
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral involvement in multiple myeloma: case report.

Abstract: SUMMARY Cerebral myeloma in a 49-year-old white man took the form of diffuse arachnoid infiltration, intracerebral perivascular cuffing, and frank intracerebral invasion.Involvement of the nervous system, one of the more common complications ofmultiple myeloma (Clarke, 1954), usually takes the form of 'myelomatous paraplegia' due either to compression of the spinal cord by extradural deposits of myeloma or, more rarely, to a collapsed vertebra (Victor et al., 1958

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
3

Year Published

1981
1981
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 8 publications
(13 reference statements)
1
14
0
3
Order By: Relevance
“…Cytological examinations revealed myeloma cell infiltration into the CSF with out plasma cells in the peripheral blood. Thereafter, several investigators reported meningeal involvement in multiple myeloma [6,7,9,11,12]. However, meningeal infil tration of myeloma cells was diagnosed morphologically in these reports.…”
Section: Discussionmentioning
confidence: 68%
“…Cytological examinations revealed myeloma cell infiltration into the CSF with out plasma cells in the peripheral blood. Thereafter, several investigators reported meningeal involvement in multiple myeloma [6,7,9,11,12]. However, meningeal infil tration of myeloma cells was diagnosed morphologically in these reports.…”
Section: Discussionmentioning
confidence: 68%
“…Este tipo de neoplasia é de origem predominantemente óssea, cuja localização principal é vertebral e menos freqüen-temente, craniana 9 . Deste modo, a complicação neurológica mais comum é a compressão medular produzida pelo crescimento progressivo extradural da massa tumoral, levando à paraplegia 6 . Ao nível craniano, o processo se localiza principalmente nos ossos da base 6 , infiltrando o espaço extradural, a órbita e a bainha dos nervos.…”
unclassified
“…Deste modo, a complicação neurológica mais comum é a compressão medular produzida pelo crescimento progressivo extradural da massa tumoral, levando à paraplegia 6 . Ao nível craniano, o processo se localiza principalmente nos ossos da base 6 , infiltrando o espaço extradural, a órbita e a bainha dos nervos. O SNC sofrerá também as conseqüências das alterações metabólicas (hipercalcemia e uremia) e da hiperviscosidade 101 presentes nesta doença.…”
unclassified
See 1 more Smart Citation
“…Multiple myelomaoccasionally presents with central nervous system involvement (1)(2)(3)(4)(5). Wereport a patient with multiple myeloma (MM)who developed cavernous sinus syndrome (CSS) and whowas found to have a plasmacytoma occupying the sphenoid sinus and the sellar region.…”
Section: Introductionmentioning
confidence: 99%